Interpretation of Dreams in QS. Yusuf Verses 1–6: Contextual Review and Classical Interpretation - Deby Cahya Kamila Gawing; Muhammad Yahya; Hasyim Haddade (Lembaga Yasin AlSys, 2026)
This study examines classical and contemporary interpretations and related literature on Surah Yusuf/12:1–6 to understand the meaning of Yusuf’s dream revelation and the ethical-pedagogical values embedded in the verses. Employing a qualitative approach with a systematic literature review design, this study analyzes selected interpretations, journal articles, theses, and books that directly discuss the verses. The data were examined thematically and comparatively to identify patterns of interpretation, the narrative function of the dream, and Qur’anic–biblical points of comparison. The findings indicate that Yusuf’s dream is positioned as a form of revelation and a prophetic sign that shapes his moral journey through patience, steadfast faith, and wisdom. Contemporary interpretations further emphasize the pedagogical function of the narrative for character education. The comparative analysis reveals narrative similarities between Qur’anic and biblical traditions, while also identifying differences in their theological emphases. This study concludes that Yusuf’s dream in Surah Yusuf/12:1–6 contains significant ethical and pedagogical values that remain relevant for contemporary character education. The study contributes to Qur’anic interpretation and Islamic education by offering a literature-based synthesis of dream revelation, prophetic morality, and character formation, with implications for integrating Yusuf’s values into character education programs and for guiding future empirical studies.